Reputation management on the IBEX 35 - González-Peláez, Marta; Marqués Pascual, Joaquín (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article investigates the management of the reputation of companies included in the Spanish stock market index IBEX 35 and its relationship with the existence, or not, of a business 'purpose', linking it with CSR management. In addition, the dilemma arises about what type of teams are more prepared, if the Communication departments or Marketing departments. For this, the collaboration of all the IBEX entities that answered a questionnaire on the matter was requested. In parallel, other reports on reputation and a part of the doctrine were analysed, crossing some data to obtain certain conclusions.